Problematika dan Solusi Pembelajaran Dikte Bahasa Arab (IMLA') Pada Siswa Madrasah Ibtidaiyah Darul Ulum Gresik - Rosyad, Muh Sabilar; Haq, Muhammad Ainul (LPPM Universitas KH.A. Wahab Hasbullah, 2024)
Imla' is a technique that is frequently used in mastering Arabic writing skills. The studens' ability of Madrasah Ibtidaiyah Darul Ulum Ujung Pangkah in reading Arabic and memorizing some of the vocabulary is not directly proportional to their knowledge of writing Arabic sentences properly and correctly. This research aims to determine the imla' learning process in fifth grade of MI Darul Ulum, in addition to uncovering the problems experienced during the imla' learning process in class and the solutions from the researcher's perspective. Based on the objectives above, this research uses a qualitative approach with a descriptive type. Data sources come from students, teachers and worksheets obtained through observation, documentation, and interview techniques. In this case, the researcher acts as the main instrument in collecting data, and then the data is analyzed using interactive descriptive techniques through the stages of data collection, condensation, presentation, and verification. The results of this research indicate that the imla' learning process in fifth grade of MI Darul Ulum has not had a positive impact, this is proven by the minimum learning completeness criteria not being achieved. The existing problems of imla' learning are divided into two, namely linguistic and non-linguistic. Based on the results of classroom observations, this problem can be overcome by increasing the variety of writing letters that are considered difficult into different words, and intensively maintaining student concentration during the learning process.